Methamphetamine abuse in former opiates addicts currently in - Noorbakhsh, Simasadat; Roohi, Mahdie; Farrahi, Hedie (International Journal of Applied Behavioral Sciences, 2016)
Background: To measure suspected abuse of the methamphetamine (MA) among methadone maintenance treatment (MMT) patients in Tehran, we studied all 206 patients who were admitted to MMT program from 2009 to 2015 to Andishe-No addiction treatment clinic. Methods: MA presence was screened in one of the random urine samples routinely taken for tests of other drugs. Results: 70 (34.3%) patients were positive for MA. A logistic regression (multivariate analyses) demonstrated that the MA abusers were more likely to be opiate abusers and less likely to be married. Conclusion: The high prevalence of MA abuse found in our patients which was rather higher than the rate of MA abuse before treatment entrance. The high rate of MA abuse in Iran needs future study Declaration Interest: None.